Perplexing Coordination Behaviour of Potentially Bridging Bipyridyl-Type Ligands in the Coordination Chemistry of Zinc and Cadmium 1,1-Dithiolate Compounds - Tiekink, Edward R. T. * (MDPI, 2018)
The X-ray structural chemistry of zinc and cadmium 1,1-dithiolates (for example, xanthate, dithiophosphate and dithiocarbamate) with potentially bridging bipyridyl-type ligands (for example, 4,40-bipyridine) is reviewed. For zinc, the xanthates and dithiophosphates uniformly form one-dimensional coordination polymers, whereas the zinc dithiocarbamates are always zero-dimensional, reflecting the exceptional chelating ability of dithiocarbamate ligands compared with xanthates and dithiophosphates. For cadmium, one-dimensional coordination polymers are usually found, reflecting the larger size of cadmium compared with zinc, but zero-dimensional aggregates are sometimes found. Steric effects associated with the 1,1-dithiolate-bound R groups are shown to influence supramolecular aggregation and, when formed, polymer topology in order to reduce steric hindrance; the nature of the bipyridyl-type ligand can also be influential. For the dithiocarbamates of both zinc and cadmium, in instances where the dithiocarbamate ligand is functionalised with hydrogen bonding potential, extended supramolecular architectures are often formed via hydrogen bonding interactions. Of particular interest is the observation that the bipyridyl-type ligands do not always bridge zinc or cadmium 1,1-dithiolates, being monodentate instead, often in the presence of hydrogen bonding. Thus, hydroxyl-O–H . . . N(pyridyl) hydrogen bonds are sometimes formed in preference toM N(pyridyl) coordinate-bonds, suggesting a competition between the two modes of association.